2023
DOI: 10.1002/epi4.12789
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of referral for long‐term EEG monitoring for Medicare beneficiaries with drug‐resistant epilepsy

Abstract: ObjectiveFor people with drug‐resistant epilepsy, the use of epilepsy surgery is low despite favorable odds of seizure freedom. To better understand surgery utilization, we explored factors associated with inpatient long‐term EEG monitoring (LTM), the first step of the presurgical pathway.MethodsUsing 2001–2018 Medicare files, we identified patients with incident drug‐resistant epilepsy using validated criteria of ≥2 distinct antiseizure medication (ASM) prescriptions and ≥1 drug‐resistant epilepsy encounter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It may also reflect legitimate concerns about frailty and surgical risk in older individuals . However, it also points to a potential bias against evaluating adults, particularly older patients and those in the Medicaid population. It is not clear why we observed higher rates of evaluation among adults compared with pediatric patients at our center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also reflect legitimate concerns about frailty and surgical risk in older individuals . However, it also points to a potential bias against evaluating adults, particularly older patients and those in the Medicaid population. It is not clear why we observed higher rates of evaluation among adults compared with pediatric patients at our center.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies of hospital admissions have found that while the number of DRE admissions has increased in recent decades, surgical volume has remained stable . Longitudinal data to characterize neurodiagnostic evaluation among patients with DRE in more diverse cohorts that approximate various population level experiences are limited …”
Section: Introductionmentioning
confidence: 99%